Decontaminant activity of volume dielectric barrier discharge against Fusarium spp. on barley seeds - Palma Rosa Rotondo; Caterina Rotolo; Petr Hoffer; Jiří Fujera; Václav Prukner; Francesco Faretra; Rita Milvia De Miccolis Angelini; Milan Šimek (Scientific Reports)
Abstract Barley is one of the basic inputs for the European malting and brewing industry. Fusarium diseases can cause significant losses in grain yield and affect crop and beer quality, leading also to contamination by mycotoxins. The aim of the work was to evaluate efficacy of volume dielectric barrier discharge under different treatment conditions and exposure times and to get benchmarks for decontamination using direct plasma treatment of seeds while preserving seed germinability. Efficacy of low-temperature plasmas impacting on surface of barley seed through short-living (nanosecond) micro-discharges was investigated for seeds artificially inoculated with Fusarium verticillioides, F. culmorum and F. graminearum. Inoculated seeds were exposed to plasma produced in a barrier discharge in synthetic air, humid air, and pure oxygen, at different exposure times. Complete inhibition of spore germination in in vitro conditions was achieved after 30 s (F. verticillioides) or 40 s (F. culmorum and F. graminearum) of plasma exposure. Efficacy of treatments in reducing colony forming units contaminating seeds was obtained after 60 s of exposure (higher than 75%) and up to 99.1% after 4 min of exposure for all three analysed Fusarium species. A reduction > 70% was always obtained under all the tested treatment conditions using different feed gases. This technology could be an environmental-friendly alternative to limit food spoilage by mycotoxigenic fungi, which can compromise the quality and safety of cereals, as this study reports the case study of malting barley.